1994
DOI: 10.2307/3869917
|View full text |Cite
|
Sign up to set email alerts
|

Two Structural Domains Mediate Two Sequential Events in g-Zein Targeting: Protein Endoplasmic Reticulum Retention and Protein Body Formation

Abstract: [gamma]-Zein is a maize storage protein synthesized by endosperm cells and stored together with [alpha]- and [beta]-zeins in specialized organelles called protein bodies. Previous studies have shown that in maize there is only one type of protein body and it is derived directly from the endoplasmic reticulum (ER). In this article, we describe the domains of [gamma]-zein involved in ER retention and the domains involved in protein body formation. To identify the signal responsible for [gamma]-zein retention in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
41
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(47 citation statements)
references
References 0 publications
5
41
1
Order By: Relevance
“…Geli et al (1994) reported that the N-terminal-repeated region of g-zein is ER located when expressed in leaves of transgenic plants but the C-terminal region is necessary for protein body formation. We have extended the first of these two conclusions: ER retention can be conferred to another protein by g-zein domains.…”
Section: Discussion a Dominant Effect Of The N-terminal Region Of G-zeinmentioning
confidence: 99%
See 4 more Smart Citations
“…Geli et al (1994) reported that the N-terminal-repeated region of g-zein is ER located when expressed in leaves of transgenic plants but the C-terminal region is necessary for protein body formation. We have extended the first of these two conclusions: ER retention can be conferred to another protein by g-zein domains.…”
Section: Discussion a Dominant Effect Of The N-terminal Region Of G-zeinmentioning
confidence: 99%
“…Zeins, however, do not have this signal. The interactions that retain zeins and cereal prolamins in general in the ER and hold protein bodies together are not clear in detail, but g-zein is able to form ER-located protein bodies also when expressed in storage (Coleman et al, 1996) or vegetative (Geli et al, 1994) tissues of transgenic plants in the absence of its partner zein subunits, indicating that no tissue-specific helping factors are required. The 27-kD g-zein polypeptide can be divided into three major domains: an N-proximal domain constituted by eight repeats of the motif PPPVHL is followed by a Pro-rich domain and finally by a Cysrich domain (Prat et al, 1985).…”
mentioning
confidence: 99%
See 3 more Smart Citations